2009
DOI: 10.1111/j.1467-8330.2009.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Fatness, Governing Bodies: The Spatialities of the Body Mass Index (BMI) in Anti‐Obesity Politics

Abstract: The Body Mass Index (BMI) is the dominant means of defining and diagnosing obesity in national and international public health policy. This paper draws on geographical engagements with Foucault's work on biopower and governmentality to question the power afforded the BMI in obesity policy. With reference to a UK public health intervention involving the measurement of children's bodies within schools, the paper questions the multiple materialities and spatialities of the BMI with reference to both its role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 51 publications
(123 reference statements)
0
121
0
Order By: Relevance
“…Other research with children and adolescents has shown that repeated body testing can result in diminished self-worth . Moreover, measurement in a group setting unavoidably elicits comparison regardless of the sharing/not sharing of results (Evans & Colls, 2009). We see this in Alva and Hannah's accounts where they compared themselves to others in the program.…”
Section: The Meaning Of Numbersmentioning
confidence: 93%
See 2 more Smart Citations
“…Other research with children and adolescents has shown that repeated body testing can result in diminished self-worth . Moreover, measurement in a group setting unavoidably elicits comparison regardless of the sharing/not sharing of results (Evans & Colls, 2009). We see this in Alva and Hannah's accounts where they compared themselves to others in the program.…”
Section: The Meaning Of Numbersmentioning
confidence: 93%
“…This, in turn can create a competitive and evaluative space where bodies can be compared to each other and/or a norm. Thus the stage is set for the possibility of success or failure (Evans & Colls, 2009). With the continued focus on testing, these young women learned to connect their sense of achievement and self-worth (at least partially) to external measures.…”
Section: The Meaning Of Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, choice is directed and governed through a host of measurements and assessments of outcomes (Miller and Rose 2008). Researchers have challenged the ways in which bodies are governed through such calculative techniques and technologies in relation to the policy attention given to obesity (Evans and Colls 2009) and alcohol (Jayne et al 2011); the ways in which different bodies are positioned as more, or less, capable of acting responsibly in contemporary public health (Colls and Evans 2008;Evans 2010;Evans et al 2011) and the ways in which particular forms of bodily matter (such as fat) come to matter (Colls 2007).…”
Section: Critical Engagements: Medicine and Health In Contemporary Bimentioning
confidence: 99%
“…BMI is used to measure physical condition and health, at both individual and population levels, and is a driver of national and international anti-obesity policies (Evans and Colls 2009;Helsedirektoratet 2010). In 2009 and 2010, 511 and 450 seamen lost their seaman's licences, respectively (Rapp 2010;Antonsen and Andersen 2011).…”
Section: Introductionmentioning
confidence: 99%